Main body characterization method, device, equipment and medium - LIU GANG (2024)
The invention provides a subject characterization method and device, equipment and a medium, relates to the technical field of artificial intelligence, can be applied to scenes such as cloud technology, artificial intelligence, intelligent traffic and auxiliary driving, and comprises the following steps: obtaining subject attribute features of a target subject, and a historical operation feature sequence generated by the target subject for historical interaction operation of multiple operation objects; the historical interaction operation comprises positive feedback operation and negative feedback operation; inputting the subject attribute feature and the historical operation feature sequence into a subject feature module of a target neural network for feature embedding, performing feature fusion based on an attention mechanism on the obtained attribute embedded feature and the operation embedded feature sequence to obtain a subject fusion feature, performing multi-interest feature extraction on the operation